Amorphous CoB nanoarray as a high-efficiency electrocatalyst for nitrite reduction to ammonia. Issue 23 (12th October 2022) - Hu, Long; Zhao, Donglin; Liu, Chengchen; Liang, Yimei; Zheng, Dongdong; Sun, Shengjun; Li, Quan; Liu, Qian; Luo, Yonglan; Liao, Yunwen; Xie, Lisi; Sun, Xuping
Abstract : Amorphous CoB nanoarray is a high-efficiency catalyst for electrocatalytic NO2 − -to-NH3 conversion, capable of attaining a large NH3 yield of 233.1 μmol h −1 cm −2 and a high faradaic efficiency of 95.2% at −0.7 V in 0.1 M Na2 SO4 with 400 ppm NO2 − . Abstract : Electrochemical reduction of nitrite (NO2 − ) is considered as an eco-friendly and sustainable strategy for simultaneous NH3 production and NO2 − removal. However, electroreduction of NO2 − is a complex reaction involving multi-electron transfer steps, thus requiring highly selective and active electrocatalysts. Herein, we report that amorphous CoB supported on TiO2 nanoarray acts as an efficient catalyst for NH3 synthesis via electrochemical NO2 − reduction. In 0.1 M Na2 SO4 with 400 ppm NO2 −, such an electrocatalyst achieves an outstanding yield of 233.1 μmol h −1 cm −2 and a high faradaic efficiency of 95.2% at −0.7 V. In addition, its performance remains stable during long-term electrolysis and cycling tests.